Latvian public service broadcasting (PSB) at a media policy crossroads on the path to public service media (PSM) - Dimants, Ainars (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2019)
This paper critically examines Latvian media policy from the point of view of public value theory, regarding the management of public service media. Since 1992, Latvian Television (LTV, 1954) and Latvian Radio (LR, 1925) officially, i.e. according to law, are independent public service media organisations, and consequently two legal entities. In fact LTV and LR are two state enterprises with one supervising council (five members) elected by parliament according to political proportionality – National Electronic Mass Media Council (the NEPLP). Since 2011, the Latvian government has been slowly deciding plans for the reform and creation of a unified PSM corporation, not just a PSB, i.e. including not only radio and TV broadcasting but a multimedia approach, especially on the Internet platform, due to media convergence. Political decisions of government and parliament for the above-mentioned intent are still wanted. Also, an initiative by LTV and NEPLP to establish a Russian language TV channel was not taken further by decision makers.